Interação planta-polinizador em espécies sincronopátricas de psychotria (rubiaceae) - Mesquita Neto, José Neiva (2013)
Plant-pollinator interactions in syncronopatric species of Psychotria (Rubiaceae). Psychotria species are commonly found in the understory of forested areas in tropical regions, and are important components for the functioning of these ecosystems. Many species of the genus are sympatric and bloom during the same period, being considered potentially syncronopatrics. For this reason, this genus has been considered as a good model to infer general patterns and mechanisms of speciation in the tropics. In the first paper of this dissertation, the interactions between potentially sympatric species of Psychotria and their pollinators were analyzed in order to verify the possible existence of sharing, specialization or generalization of pollinators and plants in the analyzed system. Then, data of secondary studies that contained identifying pollinators of Psychotria were analyzed From these data, we generated graphs and analyzes of interaction networks and niche overlap. Altogether, nine species of Psychotria and 25 species of pollinators of occurrence in the Atlantic Forest were included in the analyzes. The plant with the most generalist network is Psychotria tenuinervis and the pollinators with the highest proportion of links and consequently with more important role in the network belonged orders Lepidoptera and Hymenoptera. Psychotria species showed niche overlap in pollination and pollinator sharing. The period of greatest intensity of flowering coincided with the rainy season in the Atlantic Forest, with up to seven species coflowering. Because Psychotria species occur in sympatry and have flowering overlap and asymmetric interactions with flower visitors, it is possible that they are involved in a process of facilitation in pollination. The second paper aimed to investigate if four sympatric populations of Psychotria show pollinators sharing and pollination niche overlap . Another objective was to determine if their flowering season are synchronics. We found a dual synchrony in this system, the first in the intensity of flowering among the populations of Psychotria and the second in the increase of the abundance of flowers and pollinators. The species of Psychotria showed sharing fundamental niche of pollination and positive impact on reproductive success. However, we note that the sharing of pollinators can not be generalized to the entire system, but to the modules or pairs of species. Thus, each species of Psychotria has one or more species of preferential pollinator for sharing and that this relationship is not always reciprocal. This reinforces that the interactions among the plant species are asymmetric.